2016
DOI: 10.1186/s12933-016-0347-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality and incidence of cardiovascular diseases and type 2 diabetes in diabetic and nondiabetic obese patients undergoing gastric banding: a controlled study

Abstract: Background and aimAim of this retrospective study was to compare long-term mortality and incidence of new diseases [diabetes and cardiovascular (CV) disease] in morbidly obese diabetic and nondiabetic patients, undergoing gastric banding (LAGB) in comparison to medical treatment.Patients and methodsMedical records of obese patients [body mass index (BMI) > 35 kg/m2 undergoing LAGB (n = 385; 52 with diabetes) or medical treatment (controls, n = 681; 127 with diabetes), during the period 1995–2001 (visit 1)] wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
2
34
2
Order By: Relevance
“…13,28,59,62,63 Furthermore, the study by Eliasson et al involved mostly patients with diabetes (81% in the BS group and 90% in controls). 13,28,62,63 Again, when any one study was removed from the analysis, the OR remained consistent (0.40-0.52, P < .05). Cancer data were reported in 4 studies, and the unadjusted pooled estimates showed that mortality was also lower in the BS group than in the non-operated obese control group (OR, 0.47; 95% CI, 0.36-0.63, P < .001; I 2 = 0%, P Q = .461) ( Figure 4B).…”
Section: Long-term Mortalitymentioning
confidence: 99%
See 4 more Smart Citations
“…13,28,59,62,63 Furthermore, the study by Eliasson et al involved mostly patients with diabetes (81% in the BS group and 90% in controls). 13,28,62,63 Again, when any one study was removed from the analysis, the OR remained consistent (0.40-0.52, P < .05). Cancer data were reported in 4 studies, and the unadjusted pooled estimates showed that mortality was also lower in the BS group than in the non-operated obese control group (OR, 0.47; 95% CI, 0.36-0.63, P < .001; I 2 = 0%, P Q = .461) ( Figure 4B).…”
Section: Long-term Mortalitymentioning
confidence: 99%
“…63 Thus, the evidence suggests that BS may improve the long-term survival of obese patients and possibly decrease cardiovascular and cancer-related mortality, but these effect estimates were pooled from lower quality studies (ie, observational studies).…”
Section: Long-term Mortalitymentioning
confidence: 99%
See 3 more Smart Citations